THE IMPORTANCE OF THE TREASURY SYSTEM IN THE ACTIVITY OF STATE FINANCIAL CONTROL BODIES - Sholdorov Dilshod; Qasimova Gulyorakhan; Navruzova Guzal (American Journals, 2023)
The article presents an analysis of the current state of the effective state financial control system as a result of the reforms carried out in our country. Also, the efficiency of the state budget's implementation of the state budget and state funds, including all incomes of the state budget and state funds, including the receipts of budget organizations from extra-budgetary funds, into a single treasury account and the implementation of all their expenses from this account. This is to carry out rapid control and monitoring of the state budget, extra-budgetary funds, extra-budgetary funds of budgetary organizations, state debts and their servicing processes, to ensure the effective use of state funds, the correct movement of state financial resources. allows to gather information about
Keywords: State financial control, treasury, single treasury account